O mágico mundo de José J. Veiga e Murilo Rubião: as verdades que o insólito nos mostra - Costa, Carolina Bernardes Alves (Universidade Federal de Catalão, 2022)
This work aims to analyze the process of constitution of unusual elements within the narratives of Murilo Rubião and José J. Veiga. The literary fortune of these authors brings works that make the reader reflect on their own human condition, as well as point to antagonisms inherent to us and society, albeit in a veiled and subtle way. Through magical realism, Rubião and Veiga mark their productions by the peculiarity between the limits of reality and fantasy, the authors break with the supernatural common to fantastic stories and project the fantastic onto everyday themes. To this end, we will research into the theories of Todorov (2008) and Furtado (1980), for conceptualizing the fantastic, of Chiampi (2008) to explore magical realism and several other scholars of the life of the authors analyzed in this research, such as Amâncio (1982), Goulart (1995) and Schwartz (1981).
The magical world of José J. Veiga and Murilo Rubião: the truths that the unusual shows us
Keywords: Murilo Rubião; José J. Veiga; Fantástico; Realismo Mágico; 8.01.00.00-7 Lingüística